Identifikasi Jenis Bambu di Areal Garapan KTH Karya Makmur II dalam Kawasan Tahura Wan Abdul Rachman - Ayu Sariani; Indriyanto Indriyanto; Ceng Asmarahman (Jurnal Celebica : Jurnal Kehutanan Indonesia, 2023)
Bamboo is a non-timber forest product that has various benefits and economic values. Bamboo belongs to the Gramineae (grass) tribe. Bamboo plants have two types of clump growth, namely simpodial (clump type) and monopodial (running type). In the area cultivated by the Karya Makmur II Forest Farmers Group in Tahura Wan Abdul Rachman various types of bamboo grow on the edges of cliffs and streams. But so far there is no concrete data regarding the types of bamboo that grow in it. This study aims to identify the types of bamboo in the area cultivated by KTH Karya Makmur II in the Tahura Wan Abdul Rachman area. The research method used is exploration and direct observation in the field. The results showed that there were 5 types of bamboo found, namely betung bamboo (Dendrocalamus asper), andong bamboo (Gigantochloa pseudorundinacea), tali bamboo (Gigantochloa apus), mayan bamboo (Gigantochloa robusta), and black bamboo (Gigantochloa atroviolacea).